Survival and behavior of silver catfish, Rhamdia quelen, submitted to antibiotics and sodium chloride treatments - Luciana Segura de Andrade (Ciência Rural, 2006)
In order to evaluate the use of antibiotics andNaCl on the behavior and survival of silver catfish, Rhamdiaquelen, infested by Ichthyophthirius multifiliis and infected withAeromonas hydrophila, juveniles were treated withchloramphenicol, chloramphenicol + salt, oxytetracycline,oxytetracycline + salt and water alone (control). Fish survivalin the treatments with chloramphenicol + salt andoxytetracycline + salt was significantly higher than in the othertreatments. The treatment with chloramphenicol presentedhigher survival than the treatment with oxytetracycline andboth showed significantly higher survival than control.Swimming activity was higher in the fish treated with antibioticsand salt compared to control fish. A combination of the studiedantibiotics plus salt is more effective to treat both A. hydrophilainfection and I. multifiliis infestation in silver catfish, but sincethe use of chloramphenicol is not allowed in Brazil,oxytetracycline plus salt seems to be the best treatment option.